Enhancing Students' Understanding of Social Studies through Online Learning Media: A Study Using Quizizz - Desi Susanti; Aman Aman; Miftahuddin Mifatahuddin; Asyrul Fikri (STAI Hubbulwathan Duri, 2024)
This study evaluates the impact of the Quizizz application on junior high school students' comprehension, highlighting its potential to enhance classroom instruction through innovative and engaging learning strategies. A Classroom Action Research (CAR) approach was employed, encompassing planning, implementing, observing, and reflecting stages. The study involved 36 eighth-grade students at SMPN 3 Batang Gangsal. Data were gathered through observations, tests, and documentation. Qualitative analysis of observational data was conducted using tables and diagrams to track progress, while quantitative analysis compared student performance across two cycles. In Cycle I, the average student score was 62.4, with 38.89% (14 students) achieving scores ≥70. By Cycle II, the average score increased to 74.1, with 88.89% (32 students) meeting or exceeding the benchmark. These results demonstrate significant improvement in students' comprehension of social studies. The findings highlight the effectiveness of Quizizz as a tool for engaging students and enhancing learning outcomes. Its interactive features contributed to increased student motivation and better comprehension of social studies concepts. The Quizizz application proved to be an effective and innovative learning tool, significantly improving student comprehension. Future research should explore its application across diverse subjects and educational levels to assess its broader impact on learning outcomes.